Mosses of Gunung Senyum Recreational Forest, a tropical limestone forest in Pahang, Peninsular Malaysia - Norhazrina, N. (PhytoKeys, 2019)
Abstract. Gunung Senyum Recreational Forest harbours 59 species, two subspecies and five varieties of mosses in 32 genera and 16 families that had been identified from a total of 589 specimens collected from the area. These figures represent 11.8% out of the 558 taxa, 20.2% out of the 158 genera and 34.7% out of the 46 families of mosses reported for Peninsular Malaysia. The total also represents 14.9% of the 442 taxa, 24.0% of the 133 genera and 40.0% of the 40 families of mosses recorded in Pahang. The largest family of mosses found in this limestone forest is Calymperaceae followed by Fissidentaceae. There are two new records for Pahang, Calymperespallidum Mitt. and Taxitheliumbinsteadii Broth. & Dixon. The analysis of species similarities of mosses found in the study area with some other selected areas showed that Gunung Senyum Recreational Forest had a high percentage of species similarity with Perlis State Park at Wang Kelian, another limestone forest, at 38%. Corticol is the main habitat utilised by mosses in Gunung Senyum Recreational Forest with 47 taxa, followed by the lignicol and calcicol each with 35 and 26 taxa, respectively.